Comment définir l’humain à partir de sa diversité ? Questions épistémologiques et enjeux philosophiques - Mathilde Lequin (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Since 1995, 15 new species have been described in the hominin clade (including all forms closer to extant humans than to extant chimpanzees and bonobos). Through an approach combining epistemology and the philosophy of science, this note shows that the diversity of hominins is not only a matter of quantification, but also a biological and anthropological issue. Through a review of the history of debates on past human diversity and an analysis of the different biases that influence assessments of the number of hominin species, this note puts forward several avenues to update the theoretical framework of palaeoanthropology, by proposing a critique of the bush-like model of evolution in favour of a reticulate model, by bringing out the philosophical assumptions underlying the systematic description of new hominin species and through a discussion on the specifically anthropological dimension of past human diversity.